Emerging nanomaterials for the application of selenium removal for wastewater treatment. Issue 5 (28th July 2016) - Holmes, Andrew B.; Gu, Frank X.
Abstract : Selenium contaminated wastewater derived from global industrial activity can bioaccumulate in aquatic organisms, presenting a source of toxicity. Several classes of nanomaterials, such as nanoscale adsorbents, catalysts and reactants, have promising potential for removing selenium in to ultra-low ppb levels. Abstract : Selenium contaminated wastewater derived from global industrial activities ( i.e. coal and mineral mining, metal smelting, oil extraction and refining, and agricultural irrigation) can bioaccumulate in aquatic organisms and presents a source of toxicity for many organisms, including humans. Selenium represents an extremely difficult contaminant to remove from wastewater due to its range of solubility, toxicity, and state of matter over different oxidation states. Recently, the application of nanomaterials for removing selenium from wastewater has received increasing interest from the power generation and industrial mining sectors. Several classes of nanomaterials, such as nanoscale adsorbents, catalysts and reactants, show promising potential in removing selenium in a wide range of oxidation states. This review article provides a summary of current selenium removal technologies, highlights the gaps in these current technologies and focuses on emerging nanomaterials capable of removing selenium oxyanions from wastewater to ultra-low microgram per litre limits. Recent published literature has focused on the modification of different nanomaterials in order to achieve high surface adsorbing activity, high reactivity, selectivity and sustainable treatment capability in efforts to remove selenium oxyanions. The majority of promising nanotechnologies for selenium removal are undergoing intense research and development in efforts to get the technology into wastewater treatment markets. These nanomaterials have the ability to remove selenium contaminants to previously unachievable ultra-low levels, while implementing reliable and sustainable treatment techniques.